Variabilidade espacial de características dendrométricas da copaíba em função da aptidão agrícola em solos do Tocantins - Costa, Bárbara Suelma Souza (Universidade Federal do Tocantins, 2017)
The Copaifera langsdorffii Desf, popularly known as copaiba and oil palm, arouses great interest in presenting multiple possibilities of use, therefore it is essential to know the chemical attributes of soils and the development of the dendrometric characteristics (CAP, DAP eh) of the individuals to define The construction of soil fertility that best conditions the development of trees. In this scenario, the study of the morphological classification of soils, linked to the use of the methodology of evaluation of the agricultural aptitude of the lands is indispensable for the guarantee of the sustainability of the species and agricultural practices. The study of the relationship between the dendrometric characteristics of Copaifera langsdorffii Desf and the agricultural aptitude of the soil classes favors the understanding of the speed of the regeneration process and of the place of natural occurrence. The objective of this study was to evaluate the degree of spatial dependence of dendrometric characteristics of Copaifera langsdorffii Desf as a function of the agricultural suitability of the Tocantinense cerrado soils. It proposed to perform the morphological and chemical characterization of the soils, as well as their classification and mapping. In addition, it was also aimed to study the Agricultural Aptitude of the soil of this area and to correlate with the dendrometric characteristics of Copaifera langsdorffii Desf. The experiment was conducted at Chácara Santa Rita, located in the municipality of Cariri do Tocantins, southern Tocantins. The spatial distribution of the dendrometric characteristics and occurrence of the trees were carried out from the geostatistics, so the soil classification and classification was done according to the Brazilian Soil Classification System (SiBCS), the soil classes found were Latossolo Amarelo, Pétrico Lipoplíntico , Dystrophic Argilubic Pintossol, Yellow Red Latosol, Haplic Cambisol, Concrete Pectic Plinthsol. Subsequently, the agricultural aptitude of the lands was made using the methodology of the Agricultural Aptitude Assessment System (SAAAT). In the area they indicated aptitude for short and long cycle cultivation, pasture planted and cultivated and area without agricultural aptitude turned for the preservation of the fauna and flora. In relation to the spatial distribution of the dendrometric characteristics of Copaifera langsdorffii Desf., It was observed that there is great variability in natural dispersal environment, the trees with higher values of DAP, CAP and h are in the areas that present higher soil fertility. The occurrence of the individuals of the species Copaifera langsdorffii Desf. Is associated to different environmental conditions that they meet and not properly to different classes if soil. In the studied area has underutilized area. The use of spatial statistics as an instrument that helps in the knowledge of the dendrometric characteristics of the individuals of Copaifera langsdorffii Desf and the preparation of maps, as well as the classification of the soil and the evaluation of the lands through the proposed methodology, served as a tool of analysis and Planning of the rational use of the soil taking into account the ideal use of the land with the conservation of this natural resource.